Growth hormone treatment of growth failure secondary to total body irradiation and bone marrow transplantation. Issue 6 (June 1991) - Papadimitriou, A; Urena, M; Hamill, G; Stanhope, R; Leiper, A D
Abstract : Growth hormone was given to 13 children (nine boys, four girls) with acute leukaemia who had undergone treatment with cyclophosphamide and total body irradiation before bone marrow transplantation. Mean age at total body irradiation and bone marrow transplantation was 9.0 years (range 3.7-15.8). Endocrinological investigation was carried out at a mean of 2.0 years (range 0.4-4.0) after bone marrow transplantation. Peak serum growth hormone responses to hypoglycaemia were less than 10.0 micrograms/l (less than 20.0 mU/l) in 10, 10.5 micrograms/l (21.0 mU/l) in one, greater than 16.0 micrograms/l (greater than 32.0 mU/l) in two patients. Mean age of the patients at the start of growth hormone treatment was 12.2 years (range 5.8-18.2). The mean time between total body irradiation and bone marrow transplantation and the start of growth hormone treatment was 3.2 years (range, 1.1-5.0). Height velocity SD score (SD) increased from a mean pretreatment value of -1.27 (0.65) to + 0.22 (0.81) in the first year, +0.16 (1.11) in the second year, and +0.42 (0.71) in the third year of treatment. Height SD score (SD) changed only slightly from -1.52 (0.42) to -1.50 (0.47) in the first year, to -1.50 (0.46) in the second year, and -1.74 (0.92) in the third year. Measurement of segmental proportions showed no significant increase in subischial leg length from -0.87 (0.67) to -0.63 (0.65) in the first year, to -0.58 (0.70) in the second year, and -0.80 (1.14) in the third year of treatment. Our data indicate that children who have undergone total body irradiation and bone marrow transplantation respond to treatment with growth hormone in either of two dose regimens, with an increase in height velocity that is adequate to restore a normal growth rate but not to 'catch up', and that total body irradiation impairs not only spinal but also leg growth, possibly by a direct effect of irradiation on the epiphyses and soft tissues.